Finding a position for a firm to succeed in the seed industry - Carlson, Thomas R (Kansas State University, 2007)
The investors I am representing would like to know if they can be successful in the seed industry. They have certain skills and abilities along with industry experience that provides them with certain advantages that would allow them to succeed in the industry. The thesis or study will provide them with a detailed study of the possibilities and the challenges that are before them. To gain insight into positioning a firm in the industry, one must find a tool to help us to discover the answers to the question. I will use "Strategic Visioning in Cascade", this model outlines area of interest such as; a strategic overview, a value proposition, a market analysis, a functional analysis, financial projection and exit strategy in its total. The focus of the study will provide insight into the value proposition and market analysis. The value proposition will follow Michael Porter's Competitive Strategy analogy of cost leadership, differentiation and focus strategies. The market analysis will follow Thompson and Strickland's seven questions that lead to understanding of the selected industry.
Keywords: Seed Industry Economics; Structural change in seed industry; Corn and soybean seed industry; Dupont/Pioneer; Dow Agriscience; Monsanto; Agriculture, Agronomy (0285); Economics, Agricultural (0503); Economics, Commerce - Business (0505)